Influence of trees on heat island potential in an urban canyon - Gulten, Ayca; Aksoy, U. Teoman; Öztop, Hakan Fehmi (Elsevier, 2016)
In recent years, urban heat island became a remarkable factor which affects the climatic comfort in urban areas. In this study, the effect of heat island in Elazig, which exists on 38.41 latitude and 39.14 longitudes on east side of Turkey, was evaluated by a computational fluid dynamics program. For this purpose, simulations were made for an urban area on east-west oriented Gazi Street, which has the highest urban density in the city, and results were evaluated by heat island potential parameter. First of all, simulations were performed for 1st, 11th and 21st days of June, July and August between 9.00 and 17.00 without tree effect. Secondly, they were performed for 11th days of June, July and August by adding tree effect. The validation of the study was performed by comparing the simulation and observational results and good agreement has been obtained. Daily average HIP values without tree effect for 1st, 11th and 21st days of June are 11.88, 11.67 and 10.80 degrees C respectively. HIP values for 1st, and 21st days of July are about 11 degrees C while it is about 13.29 degrees C for 11th day. Temperature values are obtained as 12.06, 12.61 and 9.27 degrees C for studied 1st, 11th and 21st days of August, respectively. Daily average HIP values decreased by adding tree effect to 4.87 degrees C for Junellth, 2.25 degrees C for July 11th and 5.74 degrees C for August 11th. It was also found that the wind speed/direction and tree effect have a significant impact on heat island potential. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Urban heat island; Heat island potential; Computational fluid dynamics; Surface temperature; Tree effect